The Process Of Settlement Of Drug Crime Cases With Child Perpetrators Through A Restorative Justice Approach At The Semarang Police Station - Yuli Arfianto, Tri (CV. Inara, 2022)
Child protection is any activity that guarantees and protects children and their rights so that they can live, grow, develop and participate optimally in accordance with human dignity and protection from violence and discrimination. Children who violate the law are strongly influenced by several factors outside of the child because criminal acts committed by children are generally a process of imitating or being influenced by negative actions from adults or people around them. The application of criminal punishment can not fully educate children to be better, but can worsen conditions and can increase the level of child crime. Protection of children in conflict with the law is very necessary, considering that children who are dealing with the law are in situations and conditions beyond their mental and psychological abilities and are in the process of being examined at the investigation stage. Law Number 11 of 2012 concerning the Criminal Justice System for Children, has included a concept in the settlement of juvenile criminal cases, namely the concept of Restorative Justice. This concept is carried out in the settlement of criminal acts by involving the perpetrator, the victim, the family of the perpetrator / victim, and other related parties to jointly seek a fair solution by emphasizing restoration to its original state, and not retaliation. considering that children who are dealing with the law are in situations and conditions beyond their mental and psychological abilities and are in the process of being examined at the investigation stage. Law Number 11 of 2012 concerning the Criminal Justice System for Children, has included a concept in the settlement of juvenile criminal cases, namely the concept of Restorative Justice. This concept is carried out in the settlement of criminal acts by involving the perpetrator, the victim, the family of the perpetrator / victim, and other related parties to jointly seek a fair solution by emphasizing restoration to its original state, and not retaliation. considering that children who are dealing with the law are in situations and conditions beyond their mental and psychological abilities and are in the process of being examined at the investigation stage. Law Number 11 of 2012 concerning the Criminal Justice System for Children, has included a concept in the settlement of juvenile criminal cases, namely the concept of Restorative Justice. This concept is carried out in the settlement of criminal acts by involving the perpetrator, the victim, the family of the perpetrator / victim, and other related parties to jointly seek a fair solution by emphasizing restoration to its original state, and not retaliation. has included a concept in the settlement of juvenile criminal cases, namely the concept of Restorative Justice. This concept is carried out in the settlement of criminal acts by involving the perpetrator, the victim, the family of the perpetrator / victim, and other related parties to jointly seek a fair solution by emphasizing restoration to its original state, and not retaliation. has included a concept in the settlement of juvenile criminal cases, namely the concept of Restorative Justice. This concept is carried out in the settlement of criminal acts by involving the perpetrator, the victim,the family of the perpetrator / victim, and other related parties to jointly seek a fair solution by emphasizing restoration to its original state, and not retaliation.